Sistematización del diseño de un plan de acción para prevenir el estrés laboral en el área de talento humano de la empresa pública metropolitana de agua potable y saneamiento – epmaps, en el periodo noviembre 2016 - mayo 2017. - Aguilar Obando, Karen Johanna (2018)
Stress at work can be defined as a physical state or mental saturation of the worker as a result of the increasing pressure in the workplace. The main aim in this paper is to promote a healthy organizational lifestyle within the Organization in order to combat and avoid work stress in the Human Talent department, optimizing their well-being in the workplace. To make this work real, a diagnosis was made on the presence of work stress, so that a quantitative tool (survey) was elaborated and used to identify the psychosocial risks and the factors that trigger work stress. It was found that up to 90% of workers report feeling stress at work, and they associate excessive workload, inadequate communication with the rest of their colleagues and the direction of the department and the existence of inappropriate interpersonal relationships among them, up to 30% of workers report feeling displeased at their job. More than the half of respondents think that work stress is related to the growing pressure at work. Finally, an action plan was proposed to combat work stress in this department, which can be extended to other departments of the company; and it can be used as a preventive tool for work stress.